2012
DOI: 10.1128/jvi.05663-11
|View full text |Cite
|
Sign up to set email alerts
|

Borna Disease Virus Infects Human Neural Progenitor Cells and Impairs Neurogenesis

Abstract: Understanding the complex mechanisms by which infectious agents can disrupt behavior represents a major challenge. The Borna disease virus (BDV), a potential human pathogen, provides a unique model to study such mechanisms. Because BDV induces neurodegeneration in brain areas that are still undergoing maturation at the time of infection, we tested the hypothesis that BDV interferes with neurogenesis. We showed that human neural stem/progenitor cells are highly permissive to BDV, although infection does not alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 44 publications
2
53
1
4
Order By: Relevance
“…BHK-21 cells (kindly provided by the National Reference Laboratory for Orbiviruses, Laboratory for Animal Health, ANSES, Maisons-Alfort, France) were grown in Glasgow MEM (GMEM [Sigma-Aldrich]) supplemented with tryptose phosphate broth, 10% FCS, and P-S. The ovine CPT-Tert cell line (kindly provided by David Griffiths, Moredun Research Institute, Penicuik, UK) derives from choroid plexus cells (45) and was grown in Iscove's modified Dulbecco's medium (IMDM [Sigma-Aldrich]) supplemented with 10% FCS, 1% sodium pyruvate, 1 mM nonessential amino acids, and P-S. Human neural progenitor cell cultures (hNPCs) were prepared from human fetal brains (first trimester stage [see references 46 and 47 for details]). hNPCs were maintained in advanced DMEM–F-12 (Invitrogen Life Technologies) supplemented with l -glutamine (2 mM [Gibco]), apotransferrin (0.1 mg/ml [Sigma-Aldrich]), insulin (25 μg/ml [Sigma-Aldrich]), and progesterone (6.3 ng/ml [Sigma-Aldrich]).…”
Section: Methodsmentioning
confidence: 99%
“…BHK-21 cells (kindly provided by the National Reference Laboratory for Orbiviruses, Laboratory for Animal Health, ANSES, Maisons-Alfort, France) were grown in Glasgow MEM (GMEM [Sigma-Aldrich]) supplemented with tryptose phosphate broth, 10% FCS, and P-S. The ovine CPT-Tert cell line (kindly provided by David Griffiths, Moredun Research Institute, Penicuik, UK) derives from choroid plexus cells (45) and was grown in Iscove's modified Dulbecco's medium (IMDM [Sigma-Aldrich]) supplemented with 10% FCS, 1% sodium pyruvate, 1 mM nonessential amino acids, and P-S. Human neural progenitor cell cultures (hNPCs) were prepared from human fetal brains (first trimester stage [see references 46 and 47 for details]). hNPCs were maintained in advanced DMEM–F-12 (Invitrogen Life Technologies) supplemented with l -glutamine (2 mM [Gibco]), apotransferrin (0.1 mg/ml [Sigma-Aldrich]), insulin (25 μg/ml [Sigma-Aldrich]), and progesterone (6.3 ng/ml [Sigma-Aldrich]).…”
Section: Methodsmentioning
confidence: 99%
“…BDV might act as a mutagen in infected cells. Although LINE-1 is usually silenced by a host epigenetic mechanism in somatic cells, it has been reported that LINE-1 was active in human neural progenitor cells that were permissive for BDV infection [96,97].…”
Section: (B) Possible Novel Pathogenicity Of Borna Disease Virusmentioning
confidence: 99%
“…We also evaluated the level of detection of the transcriptome pipeline dedicated to embryos using a known virus present in databases: blinded transcriptome analysis of Vero cells infected at a very low multiplicity of infection (0.025 pfu/cell) with the Borna Disease virus, a non cytolytic enveloped RNA virus, allowed the detection of infection two days post infection. The virus was identified at the same time by immunofluorescence analysis and RT-PCR [16,17]. Our results strongly suggest that the hypothesis of productive infection of eggs with a virus even distant from known viruses is highly unlikely.…”
mentioning
confidence: 57%